Risk of injury-related hospitalization for children who experienced parental incarceration in Canada, 2015–2021: A population-based study - Harvey, Brooke; Croxford, Ruth; Kouyoumdjian, Fiona (International Journal of Population Data Science, 2026)
Parental incarceration is a significant adverse childhood experience linked to poorer health outcomes and increased healthcare needs among children. While international studies highlight these associations, there is limited Canadian evidence, especially regarding acute care utilization. The objective of this study was to examine the risk of injury-related hospitalization among children exposed to parental incarceration in Canada between 2015 and 2021. We conducted a retrospective cohort study using linked correctional, health, and vital statistics data from five Canadian provinces, accessed through Statistics Canada’s Social Data Linkage Environment. Parents who had been incarcerated in a provincial correctional facility were identified using the Canadian Correctional Services Survey, and their children were identified using the Canadian Vital Statistics and the Canadian Child Tax Benefit; injury-related hospital admissions were identified from the Discharge Abstract Database. Children under 18 with at least one parent incarcerated during the study period were compared to a population reference. Analyses for this work are in progress. Age-specific and age-adjusted hospitalization incidence rates will be calculated and compared to a population reference, using standardized incidence ratios and 95% confidence intervals. Injury-related hospitalization rates, overall and for specific causes, will be described by sociodemographic characteristics and timing of parental incarceration exposure. Findings will be discussed in the context of making recommendations for targeted health and social interventions to address the complex needs of children affected by parental incarceration. Improving access to care and addressing broader social determinants could reduce preventable morbidity and support better outcomes for children and their families.